PENGEMBANGAN MATERI PEMBELAJARAN MENGARANG NARASI DENGAN MEDIA GAMBAR BERSERI PADA SISWA KELAS V SEKOLAH DASAR DI KLATEN - Almasitoh, ummu Hany; Setyaningtyas, Anna Febrianty (MAGISTRA, 2013)
This research studies the development of a learning that begins with an analysis of student needs on the themes of the narrative concocted by media beamed images. On the basis of the themes of the narrative concocted by media beamed images, then prepared learning modules that are integrated in the learning of narrative writing as a result of the development of teaching materials fabricated narrative. Then the learning module is tested on students SDN 2 Barenglor and SDN 3 Karanganom, Klaten to determine the feasibility and acceptability of students and teachers at school. The research data collection techniques using non test. Non engineering tests performed by (1) observation, (2) teacher and student interviews conducted outside of school hours, (3) the questionnaire, (4) documentation. Techniques of data analysis in this study is the observation tabulated, and the results of questionnaires and interviews were identified, classified and presented as argumentative. This study uses the foundation Education Unit Level Curriculum (SBC) 2006 current so as not to give rise to new problems in achieving the target of research. However, because it is more focused on the learning aspect of the development of ideas, keruntutan thought, sharpness of thought, precision of argument, scientific development, paragraph development, development discourse, accuracy of language diversity, as well as spelling and Grammar truth, then learning more emphasis on the affective domain, the cognitive, and psychomotor. The problem in this study is âhow is the development of learning materials making up the narrative with media beamed images in Class V Elementary School?â The results indicate that students feel a sense of fun, interesting, easy to understand and very helpful when writing a narrative essay using the media beamed images and choosing environmental topics, technology and life at sea as a theme of the narrative concocted by media beamed images. So also benefited greatly from the teacher media beamed images when providing materials to write a narrative essay. Product obtained ie compose narrative learning modules using media beamed images in class V Elementary School students. Keywords:Â development research, narrative writing, media beamed images, materials development model